Expanding the Menu: Re-Imagining Film School for an Evolving Landscape - Wagner, Daniel Lincoln (Auckland University of Technology, 2016)
This research will examine two rapidly evolving industries: motion picture and tertiary education, and will explore methods for broadening specialist film skills training to include the development of capabilities that address the realities of today’s rapidly changing digital landscape. The moving image industry today is in a period of transformation and growth in both its technology and its scope. With seeds sown by the breakup of the studio system in the late 1940’s, and gathering momentum with the advent of the digital revolution over the past two decades, the business of making movies, the avenues for distributing movies, the means of watching movies - even the definition of what a movie is – have been undergoing fundamental change. There are now more ways than ever before to create, consume, and interact with moving image content. The paradigm-shifting cultural and technological transformations of recent years have given rise to wholly new models of creation, circulation, usage and spreadability of moving image storytelling. Emerging tools and methods are challenging traditional notions of story and expanding story horizons. These shifts also see redefinitions of some of the old job roles involved in creating moving image content, which, in turn, necessitates a relook into how to teach students who will soon be seeking employment in the new marketplace. Higher Education is also experiencing deep and rapid transformation internationally. The ubiquity of information available online, serious economic challenges and competition from a variety of new education models are among the forces at work which call on legacy educational institutions to relook at their mission and their delivery philosophy. Understanding the nature of teaching and learning has been developing as well, bringing new approaches to pedagogy. However, much of moving image education still has one foot in the past. Many institutions are still primarily teaching conventional approaches to film production. Many film school students will graduate into an environment that is very different from the one for which they trained. Whether working as solo practitioners or collaboratively in teams, as contractors or employees, tomorrow’s moving image graduates will be entering the evolving creative industries landscape. With much specialist knowledge now readily available online and the tools to make movies now widely affordable and able to be carried in a backpack, moving image education must quickly self-reflect and adapt to provide relevant guidance to tomorrow’s moving image creators. Through an exploration of the ways in which contemporary moving image education might refocus its content to address a rapidly changing world, this Thesis proposes an integrated, future-focused moving image programme aimed at fostering independence and lateral thinking, creative proactivity in the arena of opportunity creation, and innovative approaches to content creation and delivery. It is hoped that the programme set forth here might support moving image education to edge one small step closer to a new way of framing learning for tomorrow’s creative practitioner.
Keywords: moving image; film school; new technologies; higher education; moving image education; film; film education; emerging technologies; curriculum; programme